Síntese e caracterização físico-química de novos semicondutores orgânicos à base de tiofeno e fenileno - Silva, Marcia Dutra Ramos (2013)
In the present work, new polymers based on thiophene-phenylene were designed, synthesized, and their properties were studied by physicochemical characterization. In particular, interaction of gamma radiation and the polymer 5-(5-(10-chlorodecyloxy)-2-methoxy-4-(5- methylthiophen-2-yl)phenyl)-5\'-(2-(2-ethylhexylo-xy)-5-methoxy-4-(5-methylthiophen-2-yl) phenyl)-2,2\'-bithiophene (PTBT-46) was performed. Linking phenylene and thiophene rings in a polymer chain is known to improve, in general, optical, electrochemical, and transport properties and then, considering this, several chemical routes have been used and different dialkoxy side chains were attached to it in order to develop such materials. For such alkyl chains, halogens groups, which have a bigger cross section for gamma radiation, have been inserted. The polymers were characterized by nuclear magnetic resonance spectroscopy (1H NMR, 13C NMR), gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FTIR), optical absorption (AO), spectroelectrochemistry (in situ UV-Vis), photoluminescence (PL), photoluminescence excitation (PLE) and dc electrical conductivity measurements. Some compounds were characterized by cyclic voltammetry (CV) to compare the electronic band gap with the optical one. The monomers obtained showed interesting optical properties and one of them (TBT-25) was able to form films. Polymers of different sizes and emissions in the range that goes from green to red in the spectral region of the UVVis were synthesized. The PTBT-46 presented a unique property in the interaction with gamma radiation: the doping of the chain. This effect was observed mainly by color change, by optical measurements and the conductivity increase with increasing of radiation dose. We also checked the influence of solvent type, material concentration, and dose rate. Blue shifts with increasing of radiation dose were observed in optical measurements and were attributed to the breaking of conjugation by molecular conformational changes. This statement comes from the fact that FTIR measurements showed no break in the chain and this process was claimed to be reversible. Therefore, new luminescent conjugated polymers were obtained with great technological interest in optoelectronic area and the use of the new phenomena, semiconductor extrinsic doping processes, is promissory in detection on the ionizing radiation area.